Kecerdasan Buatan (Artificial Intelligence/ AI) dan Agama dalam Kehidupan Manusia - Hendro Setiawan; Yosep Irawan (Sekolah Tinggi Teologi Sriwijaya, 2025)
The development of artificial intelligence (AI) has significantly transformed many aspects of human life, including religion. This study aims to examine the impact of AI on religion and to identify the limits of AI’s influence on human life. Using a qualitative library research method, this study analyzes relevant literature on artificial intelligence, digital technology, and religion through content analysis and a comparative approach. The findings indicate that AI possesses advanced cognitive and technical capabilities and can surpass human performance in various intellectual tasks. However, AI lacks faith, moral awareness, and spiritual experience. Therefore, AI cannot replace the essence of religion, which is rooted in the human relationship with the Transcendent and the search for meaning beyond empirical reality. This study concludes that religion remains essential as a moral foundation and a source of meaning in the technological era.